The facts, the fights, the figures and the fora - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Seeding Solutions Volume 1. Policy options for genetic resources: People, Plants and Patents revisited By the Crucible II Group, DHF (Dag Hammarskjöld Foundation), IDRC (International Development Research Center) & IPGRI (International Plant Genetic R